Dietary Strategies for Autoimmune Disease Management: A Literature Based Review - Priyanka Tatikonda; Sumalatha Borancha; Sreeja Dodda; Rithika Shatrashi; Tejasri Mahalaxmi Panala; Yeshasree Gunjette; Narender Boggula (Asian Journal of Pharmaceutical Research and Development, 2025)
Autoimmune diseases are a group of disorders in which the host immune system mistakenly attacks its cells and tissues. This leads to chronic inflammation and damage to various organs and tissues, resulting in a wide range of symptoms and complications. The overall prevalence of autoimmune diseases worldwide is 3 to 8%, with women accounting for 78 to 85% of cases. An autoimmune disease is a condition in which the body’s immune system mistakenly attacks healthy organs and tissues, leading to excessive release of cytokines. Examples include systemic lupus erythematosus, rheumatoid arthritis, Hashimoto’s thyroiditis, and multiple sclerosis, which are occurring frequently and inflicting the burden on individuals and the health care system. Individuals with a nutrient-rich diet can help to prevent the disease progression. However, exact nutrients are not clear, but some specific diets including all nutrients can help for proper functioning of the immune system and keeps good gut health. This article explores the relationship between nutrition and autoimmune diseases,emphasizing the importance of nutrients in maintaining gut integrity and immune regulation, which includes a detailed description of gluten-free regimens, autoimmune protocol, and anti-inflammatory diets.